1977
DOI: 10.1017/s0025727300037145
|View full text |Cite
|
Sign up to set email alerts
|

The development of the virus concept as reflected in corpora of studies on individual pathogens. 4. Rabies--Two millennia of ideas and conjecture on the aetiology of a virus disease

Abstract: WHEN wRmUhBs of medical texts wish to remind their readers that virus disease is nothing new, they turn to the records of smallpox and of rabies. From antiquity, and through the centuries, the impact of smallpox on social and political history through the extent and severity of epidemics, and the high rate of mortality, has been considerable and equalled among the infectious diseases only by bubonic plague.' Rabies on the other hand never claimed large numbers of victims even in epidemic situations. In one out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 7 publications
0
8
0
3
Order By: Relevance
“…He took saliva from a rabid dog and painted it with a small brush into incisions he had made in healthy animals, including other dogs, cats, and rabbits, and the animals subsequently developed rabies (Wilkinson, 1977). However, it is unclear if Zinke had read this article and whether or not it provided the inspiration for his experiments (Wilkinson, 1977). A few years earlier, in 1793, John Hunter (1754-1809) suggested evaluating the transmissibility of rabies between species and indicated that transmission by 3 incision and transfer of infected saliva on the point of a lancet should be feasible (Hunter, 1793).…”
Section: Earliest Pathogenesis Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…He took saliva from a rabid dog and painted it with a small brush into incisions he had made in healthy animals, including other dogs, cats, and rabbits, and the animals subsequently developed rabies (Wilkinson, 1977). However, it is unclear if Zinke had read this article and whether or not it provided the inspiration for his experiments (Wilkinson, 1977). A few years earlier, in 1793, John Hunter (1754-1809) suggested evaluating the transmissibility of rabies between species and indicated that transmission by 3 incision and transfer of infected saliva on the point of a lancet should be feasible (Hunter, 1793).…”
Section: Earliest Pathogenesis Studiesmentioning
confidence: 99%
“…These experiments proved that rabies was an infectious disease. In 1821, the French neurophysiologist François Magendie (1783Magendie ( -1855 reported the transmission of rabies to a dog by inoculation of saliva from a human case of rabies (Magendie, 1821), but there was no indication that he was familiar with the previous writings of either John Hunter or Georg Zinke (Wilkinson, 1977). However, it is unclear if Zinke had read this article and whether or not it provided the inspiration for his experiments (Wilkinson, 1977).…”
Section: Earliest Pathogenesis Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…and dread it evoked in historians of the past. For a more thorough treatise, the interested reader is referred to Steele and Fernandez [ 12 ], Baer [ 13 ], and Wilkinson [ 14 ]. Most global reference languages singularly denote the terms damage, violence, fury, madness, or rage as literally synonymous with this affl iction.…”
Section: Introductionmentioning
confidence: 99%
“…En escritos de Demócrito, Aristóteles, Hipócrates y Celsus se describen las características clínicas de la rabia (Fleming, 1872). Aristóteles escribió: "la enfermedad es fatal para el perro y para cualquier animal que pueda morder, excepto del hombre" (Wilkinson, 1977). En el año 100 AC, el médico Celsus describió la rabia humana y utilizó el término hidrofobia, que es una palabra derivada del griego y significa "miedo al agua".…”
Section: Historiaunclassified